The effect of elevation on diversity and abundance of class insecta at Gunung Datuk, Negeri Sembilan - Siti Aishah Mohd Pudzi,; Noor Nasuha Abd. Aziz,; Saiyid Jalaluddin Saiyid Shaifuddin,; Idris Abd. Ghani,; Siti Khairiyah Mohd. Hatta, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2017)
Insect are among the most diverse and ecologically important organisms on the earth, but their diversity and abundance are rarely quantified. The study was set out at Gunung Datuk, Negeri Sembilan with the objective to determine the diversity and abundance of insects and to identify the differences in their distribution of different elevations of Gunung Datuk forest by using the Malaise traps. Overall, a total of 15 orders of insects comprising 1678 individuals were successfully identified. Low and high elevations recorded with both 1027 and 651 individuals collected respectively which belong to 14 orders each. Even though both elevations recorded the same number of orders, but not all orders present at low elevation were present at high elevation. High existence of flowering trees and near to stream water at low elevation make them to have more abundant insect rather than at high elevation. Diptera was found to be the most abundant order at Gunung Datuk forest with the total percentage of 51.97 followed by Hymenoptera (11.17%) and Lepidoptera (9.91%). The least number of individuals collected was Ephmeroptera with only one individual collected respectively. The Shannon Wiener Diversity Index (H’) showed that low elevation had the highest diversity with the value of H’=1.29. Meanwhile, the T-test results showed that both elevations did not differ significantly with P > 0.05. Cluster analysis revealed there were no specific patterns of abundant for insects’ order along the elavational and latitudinal gradient.